Camioleum choi, a new species in the omaliine tribe Anthophagini (Coleoptera: Staphylinidae) from Korea - Shin, Choru; Ahn, Kee-Jeong (Zootaxa, 2006)
Camioleum choi Shin & Ahn, new species (type locality: Mt. Odaesan, Korea) is described, and habitus photo and line illustrations of diagnostic features are provided for its recognition. The differences between C. loripes Lewis and C. choi are discussed.